Peningkatan Literasi Ekowisata Berkelanjutan Berbasis KLHS RTRW Pada Masyarakat Kabupaten Banggai Kepulauan - Reinal Putalan; Muh. Nur Sangadji; Rostiaty Rahmatu; Irwan Lakani; Selvy Mozin; Maulidin Kurniawan; Septian Palma Ariany (Jurnal Ilmu Sosial Terapan, 2026)
Banggai Kepulauan Regency has substantial natural, coastal, marine, karst, and tourism potential; however, these potentials are accompanied by environmental vulnerability, disaster risk, and limited community understanding of sustainable spatial planning and ecotourism management. This community service activity aimed to improve public literacy regarding sustainable ecotourism, environmental conservation, and the integration of Strategic Environmental Assessment principles into the Regional Spatial Plan of Banggai Kepulauan Regency. The activity was carried out through a participatory approach involving socialization, discussion, document review, and community-based assistance. The materials focused on the importance of protecting water resources, conserving lakes and karst ecosystems, managing waste in tourism areas, and strengthening community participation in environmentally sound spatial planning. The results showed that the activity helped participants understand the relationship between spatial planning, disaster mitigation, environmental carrying capacity, and sustainable tourism development. Community members became more aware that tourism development should not only pursue economic benefits but also consider ecological protection and social sustainability. The discussion also revealed the need for continuous assistance, clearer information on tourism management, and stronger collaboration between local government, communities, and other stakeholders. This activity indicates that environmental education based on Strategic Environmental Assessment documents can be an effective approach to strengthening community awareness and supporting sustainable development in island regions.